2019
DOI: 10.1111/hex.12953
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on shared decision making: A reflection‐quantification study

Abstract: Background Reflecting (“stop‐and‐think”) before rating may help patients consider the quality of shared decision making (SDM) and mitigate ceiling/halo effects that limit the performance of self‐reported SDM measures. Methods We asked a diverse patient sample from the United States to reflect on their care before completing the 3‐item CollaboRATE SDM measure. Study 1 focused on rephrasing CollaboRATE items to promote reflection before each item. Study 2 used 5 open‐ended questions (about what went well and wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Patient perspectives of a medical decision process often also integrate patient satisfaction with care 13,34 and other important aspects of patient experience that may not be part of the specific decision-making process evaluated by a given observer. 35 Observer ratings of shared decision making, often done by a trained assessor, are supposed to reflect the objective assessment of shared decision making happening in a specific and often single clinical consultation. This implies that, when it comes to medical decisions requiring some amount of time and several patient-clinician encounters, using a single consultation to rate shared decision making may lead to an underestimation of the occurrence and the quality of the decision making process by observers compared to the patient's point of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient perspectives of a medical decision process often also integrate patient satisfaction with care 13,34 and other important aspects of patient experience that may not be part of the specific decision-making process evaluated by a given observer. 35 Observer ratings of shared decision making, often done by a trained assessor, are supposed to reflect the objective assessment of shared decision making happening in a specific and often single clinical consultation. This implies that, when it comes to medical decisions requiring some amount of time and several patient-clinician encounters, using a single consultation to rate shared decision making may lead to an underestimation of the occurrence and the quality of the decision making process by observers compared to the patient's point of view.…”
Section: Discussionmentioning
confidence: 99%
“…On a scale of 0 to 100, the minimum OPTION-5 score was 0, the maximum was 55, and the median score (interquartile range [IQR]) was 25 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (Figure 1). The estimated proportion of observer-rating risk communication and values clarification (RCVC-observer) was 63% across all consultations (95% confidence interval [CI], 54%-70%).…”
Section: Observers' Ratings Of Shared Decision Makingmentioning
confidence: 99%
“…These self-report instruments tend to show ceiling effects (i.e., scores are generally high without much variance), 7,8 possibly due to halo effects (i.e., SDM is difficult to disentangle from other qualities attributed to the care received or from overall satisfaction). 9 Other SDM instruments are observer-based coding schemes, requiring a trained assessor to observe and code the patient-clinician conversation. This is time and resource consuming, but raters are trained in the evaluation of SDM and thus can be expected to apply stricter criteria and avoid ceiling effects.…”
mentioning
confidence: 99%
“…44,45 We recently showed that patient evaluations of the process of SDM and of the quality or sense of the final decision, that is, the outcome of SDM, are only weakly correlated. 46 This would suggest a gap in the validity of SDM process measures to the extent that they fail to award the best score to the best care. 47 Recognizing that the purpose of SDM is to contribute to care by working through how best to respond the patient's human problem, and that different modes of SDM are needed to respond to different kinds of problems, then the way to measure SDM should reflect which purpose SDM pursues in the situation under evaluation.…”
Section: Assessing Sdmmentioning
confidence: 99%